Evolution of atmospheric xenon and other noble gases inferred from Archean to Paleoproterozoic rocks. (1st July 2018) - Avice, G.; Marty, B.; Burgess, R.; Hofmann, A.; Philippot, P.; Zahnle, K.; Zakharov, D.
Abstract: We have analyzed ancient atmospheric gases trapped in fluid inclusions contained in minerals of Archean (3.3 Ga) to Paleozoic (404 Ma) rocks in an attempt to document the evolution of the elemental composition and isotopic signature of the atmosphere with time. Doing so, we aimed at understanding how physical and chemical processes acted over geological time to shape the modern atmosphere. Modern atmospheric xenon is enriched in heavy isotopes by 30–40‰ u −1 relative to Solar or Chondritic xenon. Previous studies demonstrated that, 3.3 Ga ago, atmospheric xenon was isotopically fractionated (enriched in the light isotopes) relative to the modern atmosphere, by 12.9 ± 1.2 (1σ) ‰ u −1, whereas krypton was isotopically identical to modern atmospheric Kr. Details about the specific and progressive isotopic fractionation of Xe during the Archean, originally proposed by Pujol et al. (2011), are now well established by this work. Xe isotope fractionation has evolved from 21‰ u −1 at 3.5 Ga to 12.9‰ u −1 at 3.3 Ga. The current dataset provides some evidence for stabilization of the Xe fractionation between 3.3 and 2.7 Ga. However, further studies will be needed to confirm this observation. After 2.7 Ga, the composition kept evolving and reach the modern-like atmospheric Xe composition at around 2.1 Ga ago. Xenon may be the second atmospheric element, after sulfur, to show a secular isotope evolution during the Archean that ended shortly after the Archean-Proterozoic transition. Fractionation of xenon indicates that xenon escaped from Earth, probably as an ion, and that Xe escape stopped when the atmosphere became oxygen-rich. We speculate that the Xe escape was enabled by a vigorous hydrogen escape on the early anoxic Earth. Organic hazes, scavenging isotopically heavy Xe, could also have played a role in the evolution of atmospheric Xe. For 3.3 Ga-old samples, Ar-N2 correlations are consistent with a partial pressure of nitrogen (pN2 ) in the Archean atmosphere similar to, or lower than, the modern one, thus requiring other processes than a high pN2 to keep the Earth's surface warm despite a fainter Sun. The nitrogen isotope composition of the atmosphere at 3.3 Ga was already modern-like, attesting to inefficient nitrogen escape to space since that time.